Heuristic vs Formalized Pricing in Consumer Markets: The Role of Price Perception Factors - V. V. Gerasimenko; K. V. Simonov (Управленческие науки)
In pricing management the dominating approach is applied on the basis of the classical paradigm of negative correlation between demand and price, which leads to overenthusiastic preference of price sales incentives and discount-bonus programs. However, the actual results of retailing raise doubts about unwavering fairness of this rule and unconditional effectiveness of the corresponding activities. The reason for this presumably lies in irrational perception of prices bycustomers, which probably needs to use heuristic adjustments in price management to increase retail profits. the objectives of the study is to justify the need of combining two methodological approaches for Russian retailing system when managing pricing — formalized and heuristic — by means of modeling situations of consumer choice of retail purchase and analysis of its determinants. The methodological basis combines the conceptual provisions of economic theory, as well as the theory of consumer’s behavioral analysis. Research methods: in-depth interviews with management specialists and experts, who assessed scenario cases, as well as by means of contextual and narrative analyses. Information base of the study consists of modern scientific publications and practical analysis data obtained by means of 110 in-depth interviews conducted in the second half of 2023 and the first quarter of 2024. The research findings show that price management in retailing should take into account the impact of pluralistic nature of irrational price perception and spontaneous customer reactions to prices. Practical significance: this study may facilitate Russian retailers to forecast price reactions of customers and find effective prices; it will be helpful for teaching management disciplines, and may also be in demand in the process of integration of neoclassical and behavioral models in the context of retail pricing management.